Assessing the Role of Potential Biomarkers in Antimony Susceptible and Resistant Clinical Isolates of L. donovani from India - Maharjan, Mahendra; Mandal, Swati; Madhubala, Rentala (Nepal Journal of Biotechnology, 2016)
Failure of antimonial drugs, the mainstay therapy for leishmaniasis has become an escalating problem in the treatment of Indian leishmaniasis. Using 14 clinical isolates from both visceral (VL) and post-kala-azar dermal leismaniasis (PKDL) patients, we have examined the role of ATP-binding cassette transporter (ABC transporter) gene, multidrug resistant protein A (MRPA) and two building blocks of the major thiol, trypanothione namely, ornithine decarboxylase gene (ODC) (a rate limiting enzyme in the polyamine biosynthesis) and γ-glutamylcysteine synthetase (γ-GCS) (a rate limiting enzyme in glutathione biosynthesis) in antimony resistance. Amplification of these three genes was observed in some but not all clinical isolates. Increased expression of the three RNAs as determined by real-time PCR was observed in all SAG-R clinical isolates. Significant increase in cysteine and glutathione levels was observed in the resistant isolates. Our studies report the underlying mechanism of antimony resistance in the clinical isolates.